Towards an improved understanding of proximity-to-failure in resistance training and its influence on skeletal muscle hypertrophy, neuromuscular fatigue, muscle damage, and perceived discomfort: a scoping review - Refalo, M. C.; Helms, E. R.; Hamilton, D. L.; Fyfe, J. J. (Journal of Sports Sciences, 2022)
While proximity-to-failure is considered an important resistance training (RT) prescription variable, its influence on physiological adaptations and short-term responses to RT is uncertain. Given the ambiguity in the literature, a scoping review was undertaken to summarise evidence for the influence of proximity-to-failure on muscle hypertrophy, neuromuscular fatigue, muscle damage and perceived discomfort. Literature searching was performed according to PRISMA-ScR guidelines and identified three themes of studies comparing either: i) RT performed to momentary muscular failure versus non-failure, ii) RT performed to set failure (defined as anything other than momentary muscular failure) versus non-failure, and iii) RT performed to different velocity loss thresholds. The findings highlight that no consensus definition for "failure" exists in the literature, and the proximity-to-failure achieved in "non-failure" conditions is often ambiguous and variable across studies. This poses challenges when deriving practical recommendations for manipulating proximity-to-failure in RT to achieve desired outcomes. Based on the limited available evidence, RT to set failure is likely not superior to non-failure RT for inducing muscle hypertrophy, but may exacerbate neuromuscular fatigue, muscle damage, and post-set perceived discomfort versus non-failure RT. Together, these factors may impair post-exercise recovery and subsequent performance, and may also negatively influence long-term adherence to RT.